Congenital Head and Neck Lesions - Meesa, Indu Rekha; Mukherji, Suresh K. (Journal of Pediatric Neuroradiology, 2016)
Various congenital head and neck lesions can present in the pediatric population. In this article, we will discuss some of the more common lesions encountered in the pediatric population including thyroglossal duct anomalies, dermoid cysts, branchial cleft anomalies, vascular and lymphatic malformations. Since they are encountered frequently, it is important for the radiologists to be aware of some of the common lesions and their imaging features.
Keywords: congenital; branchial cleft anomalies; thyroglossal duct cysts; dermoid cysts; vascular; lymphatic